PENYULUHAN KESEHATAN GIGI DAN MULUT PADA SISWA SEKOLAH DASAR SDN 03 ALAI KOTA PADANG DALAM RANGKA MEMPERINGATI WORLD ORAL HEALTH DAY TAHUN 2017 - Nila Kasuma; Haria Fitri; Dedi Sumantri; Firdaus Firdaus; Adriansyah Adriansyah; Satria Yandi; Widya Puspita Sari; Fildzah Nurul Fajrin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2018)
Screening for dental caries and risk for caries in young children prior to school entry couldidentify caries at an earlier and reversible stage, and lead to interventions to treat existing caries,prevent progression of caries, and reduce incidence of future lesions. Screening strategies typicallyinclude oral health risk assessment and visual examination to identify high-risk children, including thosewho already have caries. Primary care clinicians can play an important role in screening for dentalcaries. Therefore, community service activities to prevent dental caries can improve and care for dentaland oral health at the national level. Through this dedication is expected dentists can share knowledgeto the community as a form of community service. The service activities are held in SDN 03 Alai Padang, as the cooperation form with Indonesia Dental Association (PDGI) to celebrate World oral HealthDay .This activity consist counseling and mass toothbrushing.